Information Beyond Borders: LIS interacting with other disciplines - Guastavino, Catherine; Turner, James (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2014)
Proceedings of the CAIS/ACSI 2008 conference.